Pharmacognostic Study On Leaves Of Genus Grewia From Western Maharashtra - Sonawane Pradip Pundlik (International Journal of Advanced Science and Technology, 2020)
The quantitative pharmacognostic properties from species of this genus Grewia were determined using leaf powder sample. Several Grewia species are well familiar for their ethnobotanical importance and therapeutic properties. These plants have many medicinal attributes like antidiabetic, analgesic, antibiotic and antimicrobial properties. Any plant which possesses medicinal properties should be subjected to detailed pharmacognostic study so that its proper identification can be done. The perspective of present study was to carry out the pharmacognostic study viz., Sugars, Methanol, Ethanol, Pet ether, Acetone, Chloroform and Benzene from leaf powder samples of Grewia plant species from Western Maharashtra region.